Molecular characterization of Plasmodium falciparum antifolate resistance markers in Thailand between 2008 and 2016 - Sugaram, R; Suwannasin, K; Kunasol, C; Mathema, VB; Day, NPJ; Sudathip, P; Prempree, P; Dondorp, AM; Imwong, M (BMC, 2020)
Background Resistance to anti-malarials is a major threat to the control and elimination of malaria. Sulfadoxine–pyrimethamine (SP) anti-malarial treatment was used as a national policy for treatment of uncomplicated falciparum malaria in Thailand from 1973 to 1990. In order to determine whether withdrawal of this antifolate drug has led to restoration of SP sensitivity, the prevalence of genetic markers of SP resistance was assessed in historical Thai samples.